Transformers, Rescue Bots. Adventures in time and space [videorecording (DVD)]. (Shout! Factory, 2016)
The Rescue Bots will not let anything stop them from their mission of protecting Earth from dangerous forces. Join Chase, Heatwave, Blades and Boulder and a family of first responders as they travel through time and space to keep Earth safe.